Global WEIRDing: transitions in wild plant knowledge and treatment preferences in Congo hunter–gatherers. (1st June 2020) - Salali, Gul Deniz; Dyble, Mark; Chaudhary, Nikhil; Sikka, Gaurav; Derkx, Inez; Keestra, Sarai M.; Smith, Daniel; Thompson, James; Vinicius, Lucio; Migliano, Andrea Bamberg
Abstract: Abstract: Cultures around the world are converging as populations become more connected. On the one hand this increased connectedness can promote the recombination of existing cultural practices to generate new ones, but on the other it may lead to the replacement of traditional practices and global WEIRDing . Here we examine the process and causes of changes in cultural traits concerning wild plant knowledge in Mbendjele BaYaka hunter–gatherers from Congo. Our results show that the BaYaka who were born in town reported knowing and using fewer plants than the BaYaka who were born in forest camps. Plant uses lost in the town-born BaYaka related to medicine. Unlike the forest-born participants, the town-born BaYaka preferred Western medicine over traditional practices, suggesting that the observed decline of plant knowledge and use is the result of replacement of cultural practices with the new products of cumulative culture.